Preparation process of diaphragm of diaphragm compressor with long service life

By quenching, plasma co-permeation, laser cladding and coating treatment on the diaphragm compressor, the problem of short service life of the diaphragm is solved, and the wear resistance, corrosion resistance and hydrogen resistance of the diaphragm are significantly improved, which extends the service life and improves the production efficiency of the equipment.

CN119899997AInactive Publication Date: 2025-04-29FUJIAN FORESTRY VOCATIONAL TECH COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510083148.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The service life of the diaphragm compressor diaphragm is short, which leads to the equipment being prone to hydrogen embrittlement in high-pressure hydrogen environment, which leads to accelerated fatigue cracks and ultimately leads to diaphragm breakage.

Method used

A preparation process is adopted, including quenching and tempering of the metal diaphragm, followed by plasma carbon-nitrogen co-permeation treatment, followed by laser cladding of composite powders such as CoCrNi alloy powder on the surface of the diaphragm, and polyvinylidene fluoride composite coating is sprayed on the laser cladding diaphragm.

Benefits of technology

The high-life diaphragm compressor diaphragm prepared through this process significantly improves the material's wear resistance, corrosion resistance and hydrogen resistance, extends the service life of the diaphragm, reduces the inspection and maintenance costs of the equipment, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005249312610000141
    Figure BDA0005249312610000141
Patent Text Reader

Abstract

The invention relates to the technical field of compressor diaphragms, and particularly discloses a preparation process of a diaphragm compressor diaphragm with long service life, the diaphragm compressor diaphragm with long service life is prepared after the surface of a metal diaphragm is processed by processing modes such as carbonitriding, laser cladding and coating, the diaphragm is smooth in surface and has good corrosion resistance and hydrogen resistance, and the service life of the diaphragm compressor diaphragm is prolonged. And the requirements of compressor industry development are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of compressor diaphragms, and in particular to a preparation process of a long-life diaphragm compressor diaphragm. Background Art

[0002] The diaphragm compressor is a positive displacement compressor, which consists of a diaphragm, an intake valve, an exhaust valve, an oil inlet mechanism, a hydraulic adjustment mechanism, etc. The diaphragm is one of the important parts of the compressor. The working principle of the diaphragm compressor is to drive the diaphragm through the hydraulic oil to change the volume of the cylinder air chamber, and work in conjunction with the intake valve and the exhaust valve to achieve the suction-compression-output of the gas. Due to its unique diaphragm structure, the air cavity has good sealing, which isolates the oil and gas. It is widely used in compressing high pressure, high purity, flammable and explosive, toxic and harmful, highly corrosive and high sealing requirements of gases, such as hydrogen.

[0003] Compared with ordinary piston compressors, the air cavity volume and air cavity pressure of diaphragm compressors are constantly adjusted during operation. This adjustment is achieved through the reciprocating motion of the diaphragm. Therefore, the performance of the diaphragm has a great influence on the working performance of the compressor. During the operation of the compressor, due to the difference in liquid and gas pressure, the surface of the diaphragm will be subjected to the effect of alternating loads, which will cause bending and deformation, thereby causing fatigue damage to the diaphragm; the diaphragm may also contact and collide with other components during repeated compression and release, causing deformation or wear of the diaphragm, affecting the volumetric efficiency of the compressor, and then affecting the intake and exhaust state of the compressor, and even causing diaphragm rupture, resulting in equipment losses or even more serious consequences.

[0004] In addition, when compressing certain specific gases, the diaphragm will also be affected by corrosion or other factors, resulting in a shortened service life. For example, in a high-pressure hydrogen environment, hydrogen atoms gather inside the metal material, causing the material to become brittle through some mechanisms, thereby reducing the material's mechanical properties such as toughness and ductility, and ultimately causing hydrogen embrittlement in the diaphragm, causing fatigue cracks to accelerate and eventually cause the diaphragm to break.

[0005] The service life of the diaphragm is crucial to the safe and stable operation of the diaphragm compressor. At present, the service life of the compressor diaphragms manufactured in my country is generally 3 to 6 months, which is difficult to meet the needs of continuous production. Therefore, the development of long-life diaphragm compressor diaphragms plays an important role in reducing the inspection and maintenance costs of equipment, improving the production efficiency of the device, and promoting the development of the industry. Summary of the invention

[0006] The purpose of the present invention is to provide a preparation process for a diaphragm compressor diaphragm with a long service life, so as to solve the problem of short service life of the diaphragm compressor diaphragm.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] A preparation process for a long-life diaphragm compressor diaphragm, specifically comprising:

[0009] Step 1: The metal diaphragm is quenched and then tempered, and then ground and polished, and the surface is cleaned with acetone and dried to obtain a pre-treated diaphragm substrate;

[0010] Step 2: using acetylene, nitrogen and hydrogen to perform plasma carbonitriding treatment on the surface of the pretreated membrane substrate, tempering and cooling after the treatment, to obtain a co-carbonitriding treated membrane;

[0011] Step 3: Laser cladding the composite powder on the surface of the co-infiltration treated membrane, and laser remelting is performed after the cladding is completed to obtain a laser cladding membrane;

[0012] Step 4: Spray the polyvinylidene fluoride composite coating onto the surface of the laser cladding diaphragm, solidify it after spraying, and cool it to obtain a long-life diaphragm compressor diaphragm.

[0013] As a limitation of the present invention, in step 1, the quenching temperature is 850-950°C, the quenching time is 0.8-1.2h, the tempering temperature is 200-250°C, and the tempering time is 20-40min.

[0014] As a limitation of the present invention, in step 2, the acetylene flow rate is 90-98 sccm, the nitrogen flow rate is 20-25 sccm, and the hydrogen flow rate is 62-68 sccm. Acetylene is first introduced for co-diffusion for 1-3 hours, and then nitrogen and hydrogen are introduced for co-diffusion for 0.5-1.5 hours.

[0015] As a limitation of the present invention, in step 2, the process parameters during carbonitriding are: the furnace temperature is 420-470°C, the furnace pressure is 300-400Pa, the pulse voltage is 620-680V, ​​and the current is 18-22A.

[0016] As a limitation of the present invention, the composite powder in step 3 includes CoCrNi alloy powder, titanium carbide powder and titanium boride powder in a mass ratio of (65-75):(13-18):(13-18).

[0017] As a limitation of the present invention, in step 3, the process parameters during laser cladding are: laser power 900-1200 W, spot diameter 2-3 mm, powder nozzle vertical distance 16-20 mm from the substrate surface, powder feeding rate 10-12 g / min, scanning speed 1000-1400 mm / min, and argon flow rate 4-6 L / min.

[0018] As a limitation of the present invention, in step 3, the process parameters during laser remelting are: laser power of 800-1000 W, scanning speed of 800-1200 mm / min, spot diameter of 2-3 mm, and remelting temperature of 420-480°C.

[0019] As a limitation of the present invention, in step 4, the preparation method of the polyvinylidene fluoride composite coating is:

[0020] The graphene oxide and ethanol are mixed, stirred evenly, and ultrasonically dispersed for 20 to 40 minutes to obtain a graphene oxide ethanol solution, and a silane coupling agent KH-550 is added to the graphene oxide ethanol solution, and the mixture is reacted at 65 to 75° C. and 400 to 600 rpm for 3 to 5 hours. After the reaction is completed, the mixture is filtered, washed with ethanol, and dried to obtain silanized modified graphene oxide;

[0021] The polyvinylidene fluoride is dried in advance, and the silanized modified graphene oxide is added to N,N-dimethylformamide, and ultrasonically dispersed at 60-80° C. for 80-100 minutes. After the dispersion is completed, the polyvinylidene fluoride is added, stirred evenly, and bubbles are removed by ultrasonication to obtain a polyvinylidene fluoride composite coating.

[0022] As a limitation of the present invention, in the polyvinylidene fluoride composite coating, the mass ratio of silanized modified graphene oxide, polyvinylidene fluoride and N,N-dimethylformamide is (0.5-1.5):(18-22):(77-83).

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The fine carbides or carbonitrides formed by carbonitriding technology have high hardness and good corrosion resistance, which can improve the wear resistance and corrosion resistance of the material, and also help to increase the roughness, which is conducive to the next step of processing and strengthening;

[0025] CoCrNi alloy is a medium-entropy alloy with good plasticity and wear resistance, and its performance is better than that of traditional alloys. The microstructure of the CoCrNi coating obtained by laser cladding is mainly composed of dendrites and equiaxed crystals. The rapid solidification characteristics of laser cladding make the elements evenly distributed. After adding titanium carbide and titanium boride powders, the grains are refined, and the composite coating is transformed from FCC single phase to FCC+TiC+TiB2 multiphase. Under the action of fine grain strengthening and dispersion strengthening, the microhardness and wear resistance of the material are improved.

[0026] Adding silanized modified graphene oxide to polyvinylidene fluoride can play a good role in hydrogen barrier. Using silane coupling agent to modify graphene oxide can improve its compatibility with polymer coatings. When hydrogen molecules approach its surface, silanized modified graphene oxide can well capture and absorb the electrons of hydrogen atoms and form bonds with them, capturing hydrogen atoms, thereby reducing the concentration of freely diffusible hydrogen in the material. In addition, the diameter of the six-membered ring of silanized modified graphene oxide is very small, and the dense electron cloud of the π bond in the structure can also form a repulsive force on tunneling electrons, which can effectively prevent the penetration of hydrogen atoms and achieve the purpose of hydrogen barrier. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] KH-550 silane coupling agent (purity: 98%), CoCrNi alloy powder (Co: 40%, Cr: 20%), titanium carbide powder (20μm), titanium boride powder (20μm), polyvinylidene fluoride (2800Pa·S); metal diaphragm (0.4mm), elemental composition is as follows:

[0029] element C Si Mn S P Cr Ni Mo Fe content(%) 0.03 0.08 1.50 0.03 0.04 16.32 11.26 2.54 margin

[0030] Embodiment 1: A preparation process of a long-life diaphragm compressor diaphragm, specifically:

[0031] Step 1: Pretreatment of the membrane substrate

[0032] The metal diaphragm substrate is heated to 900°C for quenching treatment and kept warm for 1 hour. After the insulation is completed, it is cooled with quenching liquid. After the quenching is completed, the temperature is raised to 230°C for tempering and kept warm for 30 minutes. After the insulation is completed, it is cooled. The surface of the metal diaphragm substrate is polished with sandpaper, cleaned with acetone, and dried to obtain a pre-treated diaphragm substrate.

[0033] Step 2: Carbonitriding

[0034] The pretreated membrane substrate is placed on the cathode disk of the plasma diffusion device. After vacuuming, argon gas is first introduced to make argon ions sputter the surface of the membrane substrate to remove the passivation film on the surface. Then the temperature is raised to 450°C, the pressure in the furnace is adjusted to 350Pa, the pulse voltage is 650V, and the current is 20A. Acetylene is first introduced for co-diffusion for 2h, and then nitrogen and hydrogen are introduced for co-diffusion for 1h, wherein the acetylene flow rate is 95sccm, the nitrogen flow rate is 22sccm, and the hydrogen flow rate is 66sccm. After the co-diffusion is completed, the membrane is taken out, the temperature is raised to 230°C, tempered and kept warm for 30min, and cooled to obtain a co-diffusion treated membrane.

[0035] Step 3: Laser Cladding

[0036] CoCrNi alloy powder, titanium carbide powder and titanium boride powder were mixed in a mass ratio of 70:15:15, stirred evenly, and put into a planetary ball mill for ball milling at a ball milling speed of 240 rpm for 3 h. After the ball milling was completed, the powder was dried at 100° C. for 1 h to obtain a composite powder for standby use;

[0037] The composite powder was clad on the co-infiltration treated membrane using laser cladding equipment. Before the laser cladding started, the laser focus and the powder focus were adjusted to overlap. The parameters of the laser cladding equipment were adjusted as follows: laser power 1000W, spot diameter 2.5mm, powder nozzle vertical distance 18mm from the substrate surface, powder feeding rate 11.2g / min, scanning speed 1200mm / min, argon was used as the protective gas during the cladding process, and the argon flow rate was 5L / min. After the cladding was completed, it was cooled and waited for the next step;

[0038] After laser cladding is completed, the powder feeding channel is closed, and the laser beam is adjusted from the direction perpendicular to the diaphragm to a 45° tilt direction for laser remelting. The laser remelting parameters are set to laser power 900W, scanning speed 1000mm / min, spot diameter 2.5mm, and remelting temperature 450℃. After remelting is completed, a laser clad diaphragm is obtained.

[0039] Step 4: Coating

[0040] 0.4 g of graphene oxide was mixed with 250 mL of ethanol, stirred evenly, and ultrasonically dispersed for 30 min to obtain a graphene oxide ethanol solution. 12 mL of silane coupling agent KH-550 was added to the graphene oxide ethanol solution, and reacted at 70° C. and 500 rpm for 4 h. After the reaction was completed, the mixture was filtered, washed with ethanol, and dried to obtain silanized modified graphene oxide.

[0041] The polyvinylidene fluoride was dried at 70°C for 12h in advance, 1g of silanized modified graphene oxide was added to 79g of N,N-dimethylformamide, and ultrasonically dispersed at 70°C for 90min. After the dispersion was completed, 20g of polyvinylidene fluoride was added, stirred evenly, and bubbles were removed by ultrasonication to obtain a polyvinylidene fluoride composite coating;

[0042] The polyvinylidene fluoride composite coating is sprayed onto the surface of the laser cladding diaphragm. After the spraying is completed, it is kept at 250°C for 30 minutes for solidification and cooled to obtain a long-life diaphragm compressor diaphragm.

[0043] Embodiment 2: A preparation process of a long-life diaphragm compressor diaphragm, specifically:

[0044] Step 1: Pretreatment of the membrane substrate

[0045] The metal diaphragm substrate is heated to 900°C for quenching treatment and kept warm for 1 hour. After the insulation is completed, it is cooled with quenching liquid. After the quenching is completed, the temperature is raised to 230°C for tempering and kept warm for 30 minutes. After the insulation is completed, it is cooled. The surface of the metal diaphragm substrate is polished with sandpaper, cleaned with acetone, and dried to obtain a pre-treated diaphragm substrate.

[0046] Step 2: Carbonitriding

[0047] The pretreated membrane substrate is placed on the cathode disk of the plasma diffusion device. After vacuuming, argon gas is first introduced to make argon ions sputter the surface of the membrane substrate to remove the passivation film on the surface. Then the temperature is raised to 450°C, the pressure in the furnace is adjusted to 350Pa, the pulse voltage is 660V, and the current is 20A. Acetylene is first introduced for co-diffusion for 2h, and then nitrogen and hydrogen are introduced for co-diffusion for 1h, wherein the acetylene flow rate is 98sccm, the nitrogen flow rate is 24sccm, and the hydrogen flow rate is 68sccm. After the co-diffusion is completed, the membrane is taken out, the temperature is raised to 230°C, tempered and kept warm for 30min, and cooled to obtain a co-diffusion treated membrane.

[0048] Step 3: Laser Cladding

[0049] CoCrNi alloy powder, titanium carbide powder and titanium boride powder were mixed in a mass ratio of 70:15:15, stirred evenly, and put into a planetary ball mill for ball milling at a ball milling speed of 240 rpm for 3 h. After the ball milling was completed, the powder was dried at 100° C. for 1 h to obtain a composite powder for standby use;

[0050] The composite powder was clad on the co-infiltration treated membrane using laser cladding equipment. Before the laser cladding started, the laser focus and the powder focus were adjusted to overlap. The laser cladding equipment parameters were adjusted as follows: laser power 1000W, spot diameter 2.5mm, powder nozzle vertical distance 18mm from the substrate surface, powder feeding rate 11.5g / min, scanning speed 1100mm / min. Argon was used as the protective gas during the cladding process, and the argon flow rate was 5L / min. After the cladding was completed, it was cooled and waited for the next step.

[0051] After laser cladding is completed, the powder feeding channel is closed, and the laser beam is adjusted from the direction perpendicular to the diaphragm to a 45° tilt direction for laser remelting. The laser remelting parameters are set to laser power 900W, scanning speed 1000mm / min, spot diameter 2.5mm, and remelting temperature 450℃. After remelting is completed, a laser clad diaphragm is obtained.

[0052] Step 4: Coating

[0053] 0.4 g of graphene oxide was mixed with 250 mL of ethanol, stirred evenly, and ultrasonically dispersed for 30 min to obtain a graphene oxide ethanol solution. 12 mL of silane coupling agent KH-550 was added to the graphene oxide ethanol solution, and reacted at 70° C. and 500 rpm for 4 h. After the reaction was completed, the mixture was filtered, washed with ethanol, and dried to obtain silanized modified graphene oxide.

[0054] The polyvinylidene fluoride was dried at 70°C for 12h in advance, 1.5g of silanized modified graphene oxide was added to 78.5g of N,N-dimethylformamide, and ultrasonically dispersed at 70°C for 90min. After the dispersion was completed, 20g of polyvinylidene fluoride was added, stirred evenly, and bubbles were removed by ultrasonication to obtain a polyvinylidene fluoride composite coating;

[0055] The polyvinylidene fluoride composite coating is sprayed onto the surface of the laser cladding diaphragm. After the spraying is completed, it is kept at 250°C for 30 minutes for solidification and cooled to obtain a long-life diaphragm compressor diaphragm.

[0056] Embodiment 3: A preparation process of a long-life diaphragm compressor diaphragm, specifically:

[0057] Step 1: Pretreatment of the membrane substrate

[0058] The metal diaphragm substrate is heated to 900°C for quenching treatment and kept warm for 1 hour. After the insulation is completed, it is cooled with quenching liquid. After the quenching is completed, the temperature is raised to 230°C for tempering and kept warm for 30 minutes. After the insulation is completed, it is cooled. The surface of the metal diaphragm substrate is polished with sandpaper, cleaned with acetone, and dried to obtain a pre-treated diaphragm substrate.

[0059] Step 2: Carbonitriding

[0060] The pretreated membrane substrate is placed on the cathode disk of the plasma diffusion device. After vacuuming, argon gas is introduced first to make argon ions sputter the surface of the membrane substrate to remove the passivation film on the surface. Then the temperature is raised to 450°C, the pressure in the furnace is adjusted to 350Pa, the pulse voltage is 640V, and the current is 20A. Acetylene is introduced for co-diffusion for 2h, and then nitrogen and hydrogen are introduced for co-diffusion for 1h, wherein the acetylene flow rate is 92sccm, the nitrogen flow rate is 20sccm, and the hydrogen flow rate is 65sccm. After the co-diffusion is completed, the membrane is taken out, the temperature is raised to 230°C, tempered and kept warm for 30min, and cooled to obtain a co-diffusion treated membrane.

[0061] Step 3: Laser Cladding

[0062] CoCrNi alloy powder, titanium carbide powder and titanium boride powder were mixed in a mass ratio of 70:15:15, stirred evenly, and put into a planetary ball mill for ball milling at a ball milling speed of 240 rpm for 3 h. After the ball milling was completed, the powder was dried at 100° C. for 1 h to obtain a composite powder for standby use;

[0063] The composite powder was clad on the co-infiltration treated membrane using laser cladding equipment. Before the laser cladding started, the laser focus and the powder focus were adjusted to overlap. The parameters of the laser cladding equipment were adjusted as follows: laser power 1000W, spot diameter 2.5mm, powder nozzle vertical distance 18mm from the substrate surface, powder feeding rate 11.0g / min, scanning speed 1300mm / min, argon was used as the protective gas during the cladding process, and the argon flow rate was 5L / min. After the cladding was completed, it was cooled and waited for the next step.

[0064] After laser cladding is completed, the powder feeding channel is closed, and the laser beam is adjusted from the direction perpendicular to the diaphragm to a 45° tilt direction for laser remelting. The laser remelting parameters are set to laser power 900W, scanning speed 1000mm / min, spot diameter 2.5mm, and remelting temperature 450℃. After remelting is completed, a laser clad diaphragm is obtained.

[0065] Step 4: Coating

[0066] 0.4 g of graphene oxide was mixed with 250 mL of ethanol, stirred evenly, and ultrasonically dispersed for 30 min to obtain a graphene oxide ethanol solution. 12 mL of silane coupling agent KH-550 was added to the graphene oxide ethanol solution, and reacted at 70° C. and 500 rpm for 4 h. After the reaction was completed, the mixture was filtered, washed with ethanol, and dried to obtain silanized modified graphene oxide.

[0067] The polyvinylidene fluoride was dried at 70°C for 12h in advance, 0.8g of silanized modified graphene oxide was added to 79.2g of N,N-dimethylformamide, and ultrasonically dispersed at 70°C for 90min. After the dispersion was completed, 20g of polyvinylidene fluoride was added, stirred evenly, and bubbles were removed by ultrasonication to obtain a polyvinylidene fluoride composite coating;

[0068] The polyvinylidene fluoride composite coating is sprayed onto the surface of the laser cladding diaphragm. After the spraying is completed, it is kept at 250°C for 30 minutes for solidification and cooled to obtain a long-life diaphragm compressor diaphragm.

[0069] Based on Example 1, a control experiment was carried out, specifically Comparative Example 1 and Comparative Example 2, as described below:

[0070] Comparative Example 1: This comparative example relates to a preparation process of a diaphragm compressor diaphragm, which differs from Example 1 in that no laser cladding treatment is performed, specifically:

[0071] Step 1: Pretreatment of the membrane substrate

[0072] The metal diaphragm substrate is heated to 900°C for quenching treatment and kept warm for 1 hour. After the insulation is completed, it is cooled with quenching liquid. After the quenching is completed, the temperature is raised to 230°C for tempering and kept warm for 30 minutes. After the insulation is completed, it is cooled. The surface of the metal diaphragm substrate is polished with sandpaper, cleaned with acetone, and dried to obtain a pre-treated diaphragm substrate.

[0073] Step 2: Carbonitriding

[0074] The pretreated membrane substrate is placed on the cathode disk of the plasma diffusion device. After vacuuming, argon gas is first introduced to make argon ions sputter the surface of the membrane substrate to remove the passivation film on the surface. Then the temperature is raised to 450°C, the pressure in the furnace is adjusted to 350Pa, the pulse voltage is 650V, and the current is 20A. Acetylene is first introduced for co-diffusion for 2h, and then nitrogen and hydrogen are introduced for co-diffusion for 1h, wherein the acetylene flow rate is 95sccm, the nitrogen flow rate is 22sccm, and the hydrogen flow rate is 66sccm. After the co-diffusion is completed, the membrane is taken out, the temperature is raised to 230°C, tempered and kept warm for 30min, and cooled to obtain a co-diffusion treated membrane.

[0075] Step 3: Coating

[0076] 0.4 g of graphene oxide was mixed with 250 mL of ethanol, stirred evenly, and ultrasonically dispersed for 30 min to obtain a graphene oxide ethanol solution. 12 mL of silane coupling agent KH-550 was added to the graphene oxide ethanol solution, and reacted at 70° C. and 500 rpm for 4 h. After the reaction was completed, the mixture was filtered, washed with ethanol, and dried to obtain silanized modified graphene oxide.

[0077] The polyvinylidene fluoride was dried at 70°C for 12h in advance, 1g of silanized modified graphene oxide was added to 79g of N,N-dimethylformamide, and ultrasonically dispersed at 70°C for 90min. After the dispersion was completed, 20g of polyvinylidene fluoride was added, stirred evenly, and bubbles were removed by ultrasonication to obtain a polyvinylidene fluoride composite coating;

[0078] The polyvinylidene fluoride composite coating is sprayed onto the surface of the co-penetration treated diaphragm. After the spraying is completed, it is kept at 250° C. for 30 minutes for solidification and cooled to obtain a diaphragm compressor diaphragm.

[0079] Comparative Example 2: This comparative example relates to a preparation process for a diaphragm compressor diaphragm, which differs from Example 1 in that no silanized modified graphene oxide is added to the coating, specifically:

[0080] Step 1: Pretreatment of the membrane substrate

[0081] The metal diaphragm substrate is heated to 900°C for quenching treatment and kept warm for 1 hour. After the insulation is completed, it is cooled with quenching liquid. After the quenching is completed, the temperature is raised to 230°C for tempering and kept warm for 30 minutes. After the insulation is completed, it is cooled. The surface of the metal diaphragm substrate is polished with sandpaper, cleaned with acetone, and dried to obtain a pre-treated diaphragm substrate.

[0082] Step 2: Carbonitriding

[0083] The pretreated membrane substrate is placed on the cathode disk of the plasma diffusion device. After vacuuming, argon gas is first introduced to make argon ions sputter the surface of the membrane substrate to remove the passivation film on the surface. Then the temperature is raised to 450°C, the pressure in the furnace is adjusted to 350Pa, the pulse voltage is 650V, and the current is 20A. Acetylene is first introduced for co-diffusion for 2h, and then nitrogen and hydrogen are introduced for co-diffusion for 1h, wherein the acetylene flow rate is 95sccm, the nitrogen flow rate is 22sccm, and the hydrogen flow rate is 66sccm. After the co-diffusion is completed, the membrane is taken out, the temperature is raised to 230°C, tempered and kept warm for 30min, and cooled to obtain a co-diffusion treated membrane.

[0084] Step 3: Laser Cladding

[0085] CoCrNi alloy powder, titanium carbide powder and titanium boride powder were mixed in a mass ratio of 70:15:15, stirred evenly, and put into a planetary ball mill for ball milling at a ball milling speed of 240 rpm for 3 h. After the ball milling was completed, the powder was dried at 100° C. for 1 h to obtain a composite powder for standby use;

[0086] The composite powder was clad on the co-infiltration treated membrane using laser cladding equipment. Before the laser cladding started, the laser focus and the powder focus were adjusted to overlap. The parameters of the laser cladding equipment were adjusted as follows: laser power 1000W, spot diameter 2.5mm, powder nozzle vertical distance 18mm from the substrate surface, powder feeding rate 11.2g / min, scanning speed 1200mm / min, argon was used as the protective gas during the cladding process, and the argon flow rate was 5L / min. After the cladding was completed, it was cooled and waited for the next step;

[0087] After laser cladding is completed, the powder feeding channel is closed, and the laser beam is adjusted from the direction perpendicular to the diaphragm to a 45° tilt direction for laser remelting. The laser remelting parameters are set to laser power 900W, scanning speed 1000mm / min, spot diameter 2.5mm, and remelting temperature 450℃. After remelting is completed, a laser clad diaphragm is obtained.

[0088] Step 4: Coating

[0089] Add 20g of polyvinylidene fluoride to 80g of N,N-dimethylformamide, stir evenly, and remove bubbles by ultrasonication to obtain a polyvinylidene fluoride coating;

[0090] The polyvinylidene fluoride coating is sprayed onto the surface of the laser cladding diaphragm. After the spraying is completed, it is kept at 250°C for 30 minutes for solidification and cooled to obtain a diaphragm compressor diaphragm.

[0091] Detection experiment:

[0092] Diaphragm compressor diaphragm samples were prepared according to the preparation processes in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2, respectively.

[0093] Friction resistance test:

[0094] A reciprocating friction and wear testing machine was used to carry out friction and wear tests on the surface of the diaphragm samples. The diaphragm samples were weighed before the test. A silicon nitride ball with a radius of 4 mm was used as the grinding material. The friction rate was set to 20 mm / s, the friction time was 20 min, and the load was 10 N. After the test, the samples were weighed again to calculate the wear rate of the diaphragm samples.

[0095] Salt spray corrosion resistance test:

[0096] According to "Artificial Atmosphere Corrosion Test Salt Spray Test" (GB / T 10125-2021), the surface of the diaphragm sample was subjected to a salt spray corrosion test using the HD-E808-160A salt spray tester produced by Haida International Instrument Co., Ltd. The temperature was controlled at 35°C, the brine concentration was maintained at 5%, and the corrosion time was set to 300h. After 300h, the diaphragm sample was taken out, the appearance of the diaphragm sample was observed, and its corrosion resistance was judged.

[0097] Hydrogen permeability determination:

[0098] The test was conducted by electrochemical hydrogen permeation. The test device consisted of an anode cell and a cathode cell. The anode cell and the cathode cell were separated by the membrane sample to be tested. The adsorbed hydrogen atoms produced by the electrochemical reaction permeated into the membrane sample to be tested from the surface of one side of the cathode cell. The hydrogen that permeated through the entire membrane sample to be tested was oxidized to H on the surface of one side of the anode cell. + The electrolyte solution was 0.1 mol / L sodium hydroxide solution, the anode cell voltage was set to 0.2 V, nitrogen was introduced into the test device to remove hydrogen, and the background current was reduced to 1 μA / cm 2 After that, hydrogen is charged to the cathode tank at a current density of 0.5 mA / cm 2 When the current reaches the highest point, hydrogen charging is stopped. After recording the current density-time curve during hydrogen penetration, it is converted into a ln current density-time curve and fitted to calculate the hydrogen permeability coefficient. The smaller the hydrogen permeability coefficient, the better the hydrogen barrier performance of the material.

[0099]

[0100] Conclusion: It can be seen from the experimental data that the diaphragm compressor diaphragm prepared by the preparation process of Example 1 is superior to the diaphragm compressor diaphragm prepared by the preparation processes of Comparative Examples 1 and 2 in terms of wear resistance, corrosion resistance and hydrogen resistance. The high-life diaphragm compressor diaphragm prepared by the present invention has good wear resistance, good corrosion resistance, and excellent hydrogen resistance, and can meet the needs of long-term production. It plays an important role in reducing the inspection and maintenance costs of equipment, improving the production efficiency of the device, and promoting the development of the industry.

[0101] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A process for preparing a diaphragm for a long-life diaphragm compressor, characterized in that: Specifically: Step 1: The metal diaphragm is quenched and then tempered, and then ground and polished, and the surface is cleaned with acetone and dried to obtain a pre-treated diaphragm substrate; Step 2: using acetylene, nitrogen and hydrogen to perform plasma carbonitriding treatment on the surface of the pretreated membrane substrate, tempering and cooling after the treatment, to obtain a co-carbonitriding treated membrane; Step 3: Laser cladding the composite powder on the surface of the co-infiltration treated membrane, and laser remelting is performed after the cladding is completed to obtain a laser cladding membrane; Step 4: Spray the polyvinylidene fluoride composite coating onto the surface of the laser cladding diaphragm, solidify it after spraying, and cool it to obtain a long-life diaphragm compressor diaphragm.

2. The process for preparing a long-life diaphragm compressor diaphragm according to claim 1, characterized in that: In step 1, the quenching temperature is 850-950° C., the quenching time is 0.8-1.2 h, the tempering temperature is 200-250° C., and the tempering time is 20-40 min.

3. The process for preparing a long-life diaphragm compressor diaphragm according to claim 1, characterized in that: In step 2, the acetylene flow rate is 90-98 sccm, the nitrogen flow rate is 20-25 sccm, and the hydrogen flow rate is 62-68 sccm. Acetylene is first introduced for co-diffusion for 1-3 hours, and then nitrogen and hydrogen are introduced for co-diffusion for 0.5-1.5 hours.

4. The process for preparing a long-life diaphragm compressor diaphragm according to claim 1, characterized in that: In step 2, the process parameters for carbonitriding are: furnace temperature of 420-470°C, furnace pressure of 300-400Pa, pulse voltage of 620-680V, ​​and current of 18-22A.

5. The process for preparing a long-life diaphragm compressor diaphragm according to claim 1, characterized in that: The composite powder in step 3 includes CoCrNi alloy powder, titanium carbide powder and titanium boride powder in a mass ratio of (65-75):(13-18):(13-18).

6. The process for preparing a long-life diaphragm compressor diaphragm according to claim 1, characterized in that: In step 3, the process parameters during laser cladding are: laser power 900-1200 W, spot diameter 2-3 mm, powder nozzle vertical distance 16-20 mm from the substrate surface, powder feeding rate 10-12 g / min, scanning speed 1000-1400 mm / min, argon flow rate 4-6 L / min.

7. The process for preparing a long-life diaphragm compressor diaphragm according to claim 1, characterized in that: In step 3, the process parameters during laser remelting are: laser power of 800-1000 W, scanning speed of 800-1200 mm / min, spot diameter of 2-3 mm, and remelting temperature of 420-480°C.

8. The process for preparing a long-life diaphragm compressor diaphragm according to claim 1, characterized in that: In step 4, the preparation method of the polyvinylidene fluoride composite coating is: The graphene oxide and ethanol are mixed, stirred evenly, and ultrasonically dispersed for 20 to 40 minutes to obtain a graphene oxide ethanol solution, and a silane coupling agent KH-550 is added to the graphene oxide ethanol solution, and the mixture is reacted at 65 to 75° C. and 400 to 600 rpm for 3 to 5 hours. After the reaction is completed, the mixture is filtered, washed with ethanol, and dried to obtain silanized modified graphene oxide; The polyvinylidene fluoride is dried in advance, and the silanized modified graphene oxide is added to N,N-dimethylformamide, and ultrasonically dispersed at 60-80° C. for 80-100 minutes. After the dispersion is completed, the polyvinylidene fluoride is added, stirred evenly, and bubbles are removed by ultrasonication to obtain a polyvinylidene fluoride composite coating.

9. The method for preparing a reinforced sizing agent for glass fiber according to claim 8, characterized in that: In the polyvinylidene fluoride composite coating, the mass ratio of silanized modified graphene oxide, polyvinylidene fluoride and N,N-dimethylformamide is (0.5-1.5):(18-22):(77-83).